Investigation of the effect of communicational empowerment pattern on nursing student's communicational competency - Alireza Salar (Wolters Kluwer Medknow Publications, 2019)
INTRODUCTION: Today medical education is focusing on teaching human and communicational skills, just like the basic theories in medicine. Making effective and efficient contacts and communications are very important in nursing. Although these studies had shown that these skills are poor among nurses. Due to this, it is important to teach these skills to all health-care providers. This study aimed to investigate the effect of communicational empowerment pattern on nursing student's communicational competency. MATERIALS AND METHODS: This study was conducted on 78 senior nursing students who were chosen randomly by the census method. Respondents were divided into case and control groups. In case group, the communicational empowerment method was conducted and in control group, no interventions were done. Data were collected by communicational competency questionnaire. Data were analyzed using descriptive statistics, Pearson correlation, and t-test through IBM, SPSS version 19, United States 2016. The significance level was considered 0.05 respectfully. RESULTS: The mean age was 22.23 ± 1.80. In the case of marital status, a number of 63 respondents were single and 15 were married. The mean score of communicational competency in case group was 112.38 ± 19.20 before intervention and 128.95 ± 11.98 after intervention. In control group, the mean score of communicational competency before intervention was 107.55 ± 14.22 and after intervention, it was 117.11 ± 15.37. There was not any significant relationship between case and control groups in the mean score of communicational competency before intervention (P = 0.0187), but a significant relationship was assessed between case and control groups in the mean score of communicational competency after intervention (P < 0.001). The level named "Good" in communicational competency was increased among respondents from 56.8% to 90.9%. CONCLUSION: Using the communicational empowerment method in clinical education is possible and it increases the communicational competency.